Validation of an Argentine version of Lupus Quality of Life questionnaire. (December 2016) - Machado Escobar, M A; Yacuzzi, M S; Martinez, R N; González Lucero, L; Bellomio, V I; Santana, M; Galindo, L; Mayer, M M; Barreira, J C; Sarano, J; Gomez, G; Collado, M V; et al.
Objective: To determine reproducibility and validity of an Argentine version of the Lupus Quality of Life questionnaire (LupusQoL) and to determine cut-off values in the questionnaire. Materials and methods: One hundred and forty-seven systemic lupus erythematosus patients (American College of Rheumatology 1982/1997) were assessed from April 2014 to July 2014. Demographic and socioeconomic variables were collected, as well as SELENA/SLEDAI, Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index Score, comorbidities and treatment data. Patients completed LupusQoL-Argentine version and European Quality of Life Questionnaire (EuroQoL-5D). Internal consistency and reliability were examined. Convergent validity with EuroQoL-5D was assessed through analysis of latent classes, which established homogeneous categories from the responses of each domain of LupusQoL and for the total. Results: Out of 147 patients, 93.2% were female, mean age 36.4 ± 11.1 years, mean disease duration 2.7 ± 9 years, mean SELENA/SLEDAI 2.7 ± 3 points. The cut-off point that defined good or bad quality of life was 0.739 for EuroQoL 5D and 63 for LupusQoL. Cut-off values for each LupusQoL domain were also defined, creating two classes in each of them. There was moderate to high concordance to classify quality of life (Kappa = 0.74, 95% confidence interval = 0.54, 0.95). Conclusion: The Argentine version of LupusQoL is a valid, reliable and reproducible instrument to assess quality of life. In this study, cut-off points that allow the classification of patients regarding whether they have good or bad quality of life are established for the first time.